PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENGGELAPAN UANG OLEH APARATUR NEGARA: Studi Putusan Nomor: 83/Pid.B/2021/PN Kbu - Bambang Hartono; Aprinisa Aprinisa; Muhamad Bagas Ranata (Gapenas Publisher, 2022)
Crime is an act that is prohibited by law and whoever does something that violates the law will be punished. In addition, crime is also a form of violation of social rules. Violations determined within the limits of values upheld in a society, including the Crime of Embezzlement. The problem in this research is the criminal responsibility for the perpetrators of the crime of embezzlement of money committed by the State Civil Apparatus based on Decision Number: 83/Pid.B/2021/PN Kbu and the factors considered by the judge to provide criminal sanctions against the perpetrators of the crime of embezzlement of money committed by State Civil Apparatus based on Decision Number: 83/Pid.B/2021/PN Kbu. The research method used is the Normative Research Method. The crime of embezzlement is embezzlement which means having goods or something that is owned by someone else but the act is not a crime